Odpowiedzi

Najlepsza Odpowiedź!
2009-11-27T18:14:56+01:00
7x^-4x-6x^+4-x^+5x=7x^-6x^-x^ - 4x+5x + 4 =x + 4
-2(3a-2b)-4a(2-3a+2b)=-6a + 4b -8a + 12a^ - 8ab = -14a + 4b + 12a^ - 8ab
(4-x)(2x+5)-4= 8x + 20 - 2x^ - 5x - 4 = 3x + 16 - 2x^
(4-2x)(3x-3)-2x(3x+1)= 12x - 12 - 6x^ + 6x - 6x^ - 2x = 4x - 12- 12x^
2009-11-27T18:16:25+01:00
1 ] 7x^-6x^-x^-4x+5x+4= 0 + x + 4
2 ] = -6a+4b-8a+12a^-8ab= -14a + 4b + 12a^ - 8ab
3 ] = 4*2x + 4*5 - x*2x-x*5= 8x + 20 - 2x^ - 5x - 4= 3x+16-2x^
4 ] 4*3x-4*3-2x*3x+ 2x*3-2x*3x-2x= 12x - 12 - 6x^ +6x-6x^-2x= 16x - 12x^ - 12